Status of Community-Based Forest Management in Selected South Asian Countries: Benefits, Challenges, and Key Lessons - Bhusal, Amrita; Dhungel, Nisha; Chhetri, Pratima; Bhattarai, Shraddha; Giri, Suja; Pathak, Tek Raj; Khanal, Ashish (Journal of Sustainability and Environmental Management, 2024)
Community-based Forest management (CBFM) initiatives have been adopted to harness benefits from forests, such as carbon sequestration, weather regulation, and the conservation of vital drainage areas, while also generating income for local communities. However, there is a research gap in understanding the challenges and opportunities faced by these initiatives in South Asian countries. This study conducted a systematic literature review, focusing on the state of CBFM in Nepal, Bhutan, Sri Lanka, and Bangladesh, where these initiatives have gained significant attention. The findings indicate that CBFM initiatives in Nepal, Bangladesh, Bhutan, and Sri Lanka have yielded positive outcomes for rural livelihoods and environmental sustainability. Community-based forestry programs have a positive impact on livelihoods by providing income-generating opportunities, reducing poverty, and enhancing the economic well-being of local communities in these countries. Moreover, these initiatives have contributed to environmental conservation through increased forest cover, biodiversity preservation, and a reduction in deforestation. Social inclusion and empowerment have been promoted, with an emphasis on engaging marginalised groups. Despite these successes, challenges persist in resource availability, governance, and legal frameworks. Adaptive management, income diversification, and sustainable forest practices are critical lessons. Community forestry presents an opportunity for sustainable development that integrates environmental conservation, economic progress, and social well-being, with the potential to serve as a model for holistic and sustainable development in the region. This review emphasises the importance of addressing inequalities, improving governance, and strengthening institutional support in CBFM initiatives to unlock their full potential for sustainable development and forest conservation in these selected South Asian countries.